DUKUNGAN SOSIAL KELUARGA SEBAGAI UPAYA PENCEGAHAN STRES PADA LANSIA DENGAN ANDROPAUSE DI DESA GEBANG WILAYAH KERJA PUSKESMAS PATRANG KABUPATEN JEMBER - Asmaningrum, Nurfika; Wijaya, Dodi; Wijaya, Chandra Aji (FKM - UNEJ, 2014)
Andropause is a group of symptoms and complaints of men as a result of the reduction in the testosterone level. Andropause occurs on men over their middle age and the symptoms, signs and complaints are similar to womenâs menopause. A good family social support can be reducedÂ stress levels. The aim of this study was to determine the correlation between family social support and the stress levels in andropausal elderly at Gebang in Patrang Health Center. The study was a survey analytical research with cross sectional approach. Method of collecting sample is purposive sampling with 88 andropausal elderly aged over sixty years. Data were analyzed by chi-square test. Based on statistical testâs result the value p is 0.000 with a significance level (alpha) of 0.05. This the p value is lower than the significant level (p less than alpha) which means that there is a correlation between family social support and the stress levels in andropausal elderly at Patrang Health Center, Jember. The recommendation of this study is to improve elderly knowledge regarding andropause and to implicate family members during examining elderly regarding andropause. Keywords : family social support, stress level, andropause